2014
DOI: 10.1371/journal.pone.0096593
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Signaling at the Level of GLI Regulates Downstream Gene Expression and Inhibits Proliferation of Canine Osteosarcoma Cells

Abstract: The Hedgehog-GLI signaling pathway is active in a variety of human malignancies and is known to contribute to the growth and survival of human osteosarcoma cells. In this study, we examined the expression and regulation of GLI transcription factors in multiple canine osteosarcoma cell lines and analyzed the effects of inhibiting GLI with GANT61, a GLI-specific inhibitor. Compared with normal canine osteoblasts, real-time PCR showed that GLI1 and GLI2 were highly expressed in two out of three cell lines and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
5
29
1
1
Order By: Relevance
“…Taking all these findings into account, we speculate that the epigenetic silencing of gli2 by hypermethylation is an important early event in the course of incomplete closure of the neural tube. GLI2 functions downstream of the Shh pathway and targets gli1 and ptch1, and a high level of GLI protein expression is often indicative of activated Shh signaling [27]. The present results found that inhibition of gli2 expression was accompanied by the decreased expression of gli1 but not ptch1, which is considered to be a repressor of the Shh pathway.…”
Section: Discussionsupporting
confidence: 53%
“…Taking all these findings into account, we speculate that the epigenetic silencing of gli2 by hypermethylation is an important early event in the course of incomplete closure of the neural tube. GLI2 functions downstream of the Shh pathway and targets gli1 and ptch1, and a high level of GLI protein expression is often indicative of activated Shh signaling [27]. The present results found that inhibition of gli2 expression was accompanied by the decreased expression of gli1 but not ptch1, which is considered to be a repressor of the Shh pathway.…”
Section: Discussionsupporting
confidence: 53%
“…Three canine OSA cell lines (Abrams, D17, and Moresco) and three human OSA cell lines (U2OS, SAOS-2, and LM7) were used in this study. The Abrams and Moresco cell lines were a gift from Dr. Douglas Thamm and Colorado State University [ 14 17 ]. The D17 cell line is derived from an osteosarcoma lung metastasis and was purchased from ATCC (Manassas, VA, Cat# CCL-183) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Abrams and Moresco cell lines were a gift from Dr. Douglas Thamm and Colorado State University [ 14 17 ]. The D17 cell line is derived from an osteosarcoma lung metastasis and was purchased from ATCC (Manassas, VA, Cat# CCL-183) [ 16 , 17 ]. The U20S, SAOS-2, and LM7 cell lines were obtained from the MD Anderson Characterized Cell Line Core Facility [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Кроме того PTCH1 является геном-мишенью для факторов транскрипции GLI, которые изменяют экспрессию мРНК PTCH1, что наблюдалось в 50% клеточных линий медуллобластомы и астроцитомы [15][16][17].…”
Section: белки образующие путь Hedgehogunclassified